THE RELIEFS OF RAMAYANA AND KRÌ£SÌ£NÌ£A STORY AT LARA JONGGRANG TEMPLE AND REIGN SHIFT OF THE ANCIENT MATARAM IN 9TH CENTURY AD: RELIEF RAMAYANA DAN CERITA KRÌ£SÌ£NÌ£A DI CANDI LARA JONGGRANG DAN PERGANTIAN KEKUASAAN MATARAM KUNA ABAD KE 9 MASEHI - Restiyadi, Andri (Berkala Arkeologi, 2020)
Abstract Lara Jonggrang is one of the temples in Java that attracts several researchers from various disciplines. The abundance of discussion about this temple does not necessarily close the possibility of new discussion or merely reinterpreting old problems through new approaches. One of the aims of this study is to reopen the old discourse about Lara Jonggrang Temple which is considered to have reached the final stage through research questions, What is the relation between the reliefs of the RÄmÄyana story and the Ká¹›á¹£á¹‡a story in Lara Jonggrang Temple and the transfer of power in the Ancient Mataram in 9th Century AD? Through a descriptive-analytical method, this study found several things that have been considered final have still kept a few surprises from new interpretations. Through this article, it is shown that Rakai Pikatan and Rakai Kayuwangi play a role as a milestone for the construction, inauguration, and carving of story reliefs in Lara Jonggrang Temple. In addition, the existence of the two reliefs is also related to the process of transfer of power in the Ancient Mataram in 9th Century AD. Abstrak Lara Jonggrang merupakan salah satu candi di Jawa yang menarik minat beberapa peneliti dari berbagai disiplin ilmu. Melimpahnya bahasan tentang candi ini tidak serta merta menutup kemungkinan bahasan baru atau hanya sekedar menginterpretasikan kembali permasalahan-permasalahan lama melalui metode pendekatan baru. Adapun salah satu tujuan dari artikel ini adalah membuka kembali wacana lama tentang Percandian Lara Jonggrang yang dianggap telah mencapai tahap final melalui pertanyaan penelitian. Apakah kaitan antara relief cerita RÄmÄyana dan Cerita KrÌ£sÌ£nÌ£a di Percandian Lara Jonggrang dengan pergantian kekuasaan Mataran Kuna Abad IX Masehi? Melalui penelitian yang bersifat deskriptif-analitis, ternyata beberapa hal yang selama ini dianggap telah final masih menyimpan beberapa kejutan interpretasi baru. Melalui artikel ini, ditunjukkan bahwa Rakai Pikatan dan Rakai Kayuwangi berperan sebagai tonggak pembangunan, peresmian, dan pemahatan relief cerita di Percandian Lara Jonggrang. Selain itu, keberadaan kedua relief cerita tersebut juga berkaitan dengan proses pergantian kekuasaan Mataram Kuna Abad ke - 9 Masehi.